Challenges in English-medium instruction (EMI) at a Japanese university - Toh, Glenn (2021)
This paper concerns English-medium instruction (EMI) and begins with an overview of issues relating to EMI initiatives in higher education as documented in the literature. Following this, the case of a Japanese university's attempt to introduce EMI into the curriculum of a newly setup liberal arts faculty is discussed. Conclusions about challenges that can follow policy initiatives to introduce EMI are drawn from this discussion. Outcomes and implications of different ways of understanding and/or conceptualizing the role of English in higher education and EMI are examined critically. The issues surfaced have implications for EMI policy making and implementation, bearing in mind the negotiations that need to take place given the workings of opposing forces: (1) those which reify homogenizing discourses about language, power and education; versus (2) those which accommodate the contextually particularized aspects of teaching and learning and the characteristically heterogeneous and intersectional nature of teacher and learner subjectivities.